Development of a Supplementary English Book for the 6th Grade Students of Elementary School - Bernad Ahmed Biyongko Tetuko; Astuti, Endang Setiyo; Indrawati Pusparini (UIBU, 2024)
This study aimed to develop an English Student Supplementary Book for the Sixth Grade Students in a rural Indonesian context where English is taught by non-specialist teachers. The research employed a Research and Development (R&D) method using the ADDIE instructional design model, encompassing analysis, design, development, implementation, and evaluation. The needs analysis revealed limited availability of qualified English teachers and a lack of appropriate supplementary materials aligned with the Merdeka Curriculum. Based on these results, a companion book emphasizing contextual content, visual support, and clear instructional guidance was developed and validated by material and media experts. The product was then implemented in the 6th grade classroom over four instructional sessions. Data were collected through expert validation sheets, classroom observations, student questionnaires, and teacher questionnaires. The results indicated that the developed book achieved medium-high level of feasibility, improved student engagement and motivation, and enhanced teacher confidence in delivering English lessons. The study concludes that a well-designed supplementary book can function as an effective pedagogical scaffold for both learners and non-specialist teachers in elementary English education.